2002
DOI: 10.1590/s0037-86822002000200002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between protein-energy malnutrition, vitamin A, and parasitoses in children living in Brasília

Abstract: It is still controversial whether intestinal parasitic infections can influence the nutritional status of children. The relationship between protein-energy malnutrition, vitamin A and parasitic infections was evaluated in 124 children. The food intake estimated by recall method was generally low and poor. Seventy five percent of the children were infected with intestinal parasites. The mean+/-SD weight-for-age and height-for-age Z-score were skewed one standard deviation to the left, when compared to normal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 31 publications
4
32
0
10
Order By: Relevance
“…Studies relating AIDS patients to opportunistic infections have shown that HAART has contributed to HIV infection control and to the reconstitution of patient immune systems, leading to a reduction in the occurrence of opportunistic infections, including those caused by intestinal parasites (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies relating AIDS patients to opportunistic infections have shown that HAART has contributed to HIV infection control and to the reconstitution of patient immune systems, leading to a reduction in the occurrence of opportunistic infections, including those caused by intestinal parasites (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that prolonged use of HAART, particularly of protease inhibitors, has an important impact on user nutritional status. The relationship between infections caused by intestinal parasites and some nutritional indicators has been proven in numerous studies involving nutritional status, infection prevalence and intensity (14)(15)(16)(17)(18)(19)(20). Malnutrition has a serious influence on immunity aspects, including the production of cytokines and antibodies, particularly Th2 profile (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…34 In contrast, previous reports from Brazil and Kenya found no association between intestinal parasitic infections and low serum retinol concentrations. 8,28 Moreover, a study aimed at investigating the effects of ascariasis on vitamin A in 24 children 4-10 years of age in a slum area of Dhaka City, Bangladesh, concluded that there was no association between ascariasis and malabsorption of vitamin A. 35 The authors also found no correlation between serum retinol concentration and intensities of A. lumbricoides infection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies among children in areas where G. duodenalis is hyperendemic found that Giardia infection has no adverse impact on their growth and vitamin A status. 8,36,37 These inconsistencies could be caused by differences in study population and study design. The subjects of the present study were Aboriginal children residing in remote area where poverty and many health problems, including malnutrition and intestinal parasitic infections, prevail, and these conditions make it more likely that complications of infection will develop in these children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation